(untitled) (Research, Society and Development, 2021)
Monitoring of the condition of railway systems has been widely used to support the assessment of the integrity of its structures and infrastructures. Permanent way geometric inspection is one of the main methods used for maintenance plans elaboration in railway networks. It is known that interventions are based on indications of nonconformities, according to intervals assumption for the analyzed parameters. However, even with this inspection, derailments originated in superstructure continues to occur. This paper presents the use of an inertial device in six railway sections, to complement the geometric inspections and prioritize maintenance scale. The execution of this study is justified because the equipment commonly used in track dynamics measurement have high prices and high complexity of installation. The accelerometer used is inexpensive and easy to apply. The mentioned device was able to identify critical points of vehicle-path interaction, that did not present geometry exception.